Existence and Estimates of Solutions for Various Elliptic Equation Models - Jiang, Yongsheng (Curtin University, 2017)
The thesis is devoted to studying the existence and estimates of solutions for various elliptic equations. We establish the partial Schauder estimates to a sub-elliptic equation by using a new estimate of the Newton potential. By using the truncated technique we establish the sufficient condition for the existence of the solution to a nonlinear elliptic equation with negative exponent. A new variational functional is developed to study a 2-dimensional Minkowski problem.